From combustion engines to electric vehicles: a study of technological path creation and disruption in Germany - Tilman Altenburg (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Mitigating climate change by reducing carbon emissions is one of the biggest and most complex issues the world has ever faced. Technological innovation plays a major role in taking on this challenge. Old and new industrial powers alike are increasingly reforming their policy frameworks to encourage low-carbon investment and innovation. The research project “Technological trajectories for low-carbon innovation in China, Europe and India” explored to what extent, how and why technological pathways differ across countries. Case studies were conducted in electromobility and wind power technologies. Evolutionary economics has demonstrated how initial choices of technologies and institutions preclude certain options at later stages; hence, innovations evolve in an incremental and cumulative way, resulting in context-specific technological pathways. How industries adapt, which alternatives emerge, how rapidly they become competitive and eventually substitute the incumbent technologies therefore follow country-specific technological pathways. This case study deals with electromobility in Germany. Germany adopted a National Electromobility Strategy to make it a lead market and lead provider for electromobility. The lead market target, however, is not likely to be achieved – due to the German industry's and consumers' preference for high-powered cars and due to limited government commitment to accelerate the transition via ambitious emissions targets or subsidies. The target to become a lead provider may be more realistic. While Germany has so far been a latecomer to battery-electric and hybrid powertrain technologies, lagging several years behind Japanese, French, Korean and US manufacturers, series production of battery-electric and plug-in hybrid vehicles appears to have been taking off since 2013/14. This reflects the overall innovative strengths of the German automotive innovation system, rather than particularly conducive home market conditions for electromobility. The German automotive industry's incremental shift to alternative powertrains displays a number of country-specific characteristics. These include a leading role in hybridisation strategies in the up-market segment where German OEMs offer `green lifestyle' cars that do not compromise on power, performance and driving pleasure but use high-tech solutions to increase energy efficiency. As another element of competitive specialisation, modularisation and standardisation are consequently used to ensure that customers can choose among a range of powertrain alternatives without compromising on the expected comfort, while at the same time economies of scale can be exploited to keep costs low. Some analysts also expect specific German developments in related services, such as intermodal transport services or smart grid technologies, but these are not yet observable.
Keywords: 330; Umwelt; Ökosysteme und Ressourcen; Technologie und Innovation